2016
DOI: 10.1002/pd.4804
|View full text |Cite
|
Sign up to set email alerts
|

The implications of non-invasive prenatal testing failures: a review of an under-discussed phenomenon

Abstract: Introduction Non-invasive prenatal testing (NIPT) using cell-free DNA in maternal blood is a relatively new screening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 59 publications
6
108
1
4
Order By: Relevance
“…In our manuscript, however, our aim was not to evaluate the methods' respective virtues on rare cases, but rather to assess the analytical performance and clinical impact for a very common occurrence: pregnancies with low fetal fraction. The SNP method routinely no‐calls low‐fetal‐fraction samples, and publications about the SNP method (e.g., Ryan et al 6) effectively inflate calculations of sensitivity by omitting the affected fetuses that are known to be enriched in the low‐fetal‐fraction patients who received no test result 10. By contrast, our analysis importantly and robustly suggests that for low‐fetal‐fraction pregnancies—common among patients with high BMI, at early gestational age, and with trisomy 13 or 18—the WGS method maintains high sensitivity, thereby yielding fewer false negatives, fewer no‐calls, and fewer unnecessary invasive procedures than the SNP method.…”
mentioning
confidence: 99%
“…In our manuscript, however, our aim was not to evaluate the methods' respective virtues on rare cases, but rather to assess the analytical performance and clinical impact for a very common occurrence: pregnancies with low fetal fraction. The SNP method routinely no‐calls low‐fetal‐fraction samples, and publications about the SNP method (e.g., Ryan et al 6) effectively inflate calculations of sensitivity by omitting the affected fetuses that are known to be enriched in the low‐fetal‐fraction patients who received no test result 10. By contrast, our analysis importantly and robustly suggests that for low‐fetal‐fraction pregnancies—common among patients with high BMI, at early gestational age, and with trisomy 13 or 18—the WGS method maintains high sensitivity, thereby yielding fewer false negatives, fewer no‐calls, and fewer unnecessary invasive procedures than the SNP method.…”
mentioning
confidence: 99%
“…These obstacles are more pronounced when the starting material is suboptimal, like the presence of amplification inhibitors or low fetal fraction: it has been shown that patients medicated with low molecular weight heparin have smaller total cfDNA fragments with an unusual high GC content [16]. Also, a fetal fraction below 4% is mainly responsible for test failures of targeted enrichment based NIPT approaches [7]. To overcome these biases, it is necessary to make targeted enrichment approaches very redundant, e.g.…”
Section: Methods Of Niptmentioning
confidence: 99%
“…Especially low fetal fraction is responsible for test failures in 0.5%-6.1% of all cases. Another parameter for the impossibility of obtaining a NIPT result was suggested to be the methodical approach: in a recent study, targeted enrichment based approaches seemed to exhibit higher failure rates than MPS based approaches (~3%-6% versus ~2%) [7]. It is of note, that two MPS based NIPT studies were excluded from failure rate calculation, as unclassified results were excluded from their test statistic calculation [8,38].…”
Section: The Performance Of Niptmentioning
confidence: 99%
See 2 more Smart Citations